English: How Democracy-Promotion is used in the European Union's Prevention of Terrorism in the Southern Mediterranean - Jonasson, Ann-Kristin (Journal of Regional Security, 2022)
Terrorism is a horror haunting the world. Different approaches are used to fight terrorism internationally, focusing on security- as well as social-policy. In policy, the European Union poses democracy-promotion as one social-policy approach to prevent terrorism. Democracy is supposed to create resilient societies, resistant to terrorism. However, research on whether democracy prevents terrorism is inconclusive. Indeed, insufficient democratisation may spur terrorism and, unless wisely handled, prevention of terrorism might instead cause it. To unravel how the EU uses democracy-promotion to prevent terrorism in the southern Mediterranean is therefore crucial. Based on interviews with EU-representatives, this article concludes that the EU’s external action does not reflect the policy-documents’ focus on democracy-promotion in preventing terrorism. While respondents regard democracy-promotion as important in preventing terrorism, it is not prioritised. Instead, terrorism-prevention is largely securitised, following the lead of Mediterranean partner-states. Such securitisation coupled with insufficient democratisation risk causing instead of preventing terrorism.